Harbour Street - Cleeves, Ann (Cleeves, Ann. Vera Stanhope series, 2016)
Told with piercing prose and a forensic eye, Ann Cleeves' gripping new novel explores what happens when a community closes ranks to protect their own--and at what point silent witnesses become complicit. -- Amazon.com.